The Relationship Between Social Support and Self-esteem in People with HIV/AIDS - Marlina, Marlina; Yolanda, Yola (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2025)
Background: People with HIV/AIDS experience both physical and emotional challenges. The existence of stigma and discrimination significantly affects their self-esteem. However, limited research has explored the direct relationship between social support and self-esteem within healthcare settings, particularly in Indonesia. Understanding this relationship is crucial for developing effective psychosocial interventions. This research aims to determine the relationship between social support and self-esteem in people with HIV/AIDS at VCT Polyclinic RSUP Dr. M. Djamil Padang Methods: This study used a cross-sectional design conducted between January and August 2024. Data collection took place from June 3 to June 26, 2024, at the VCT Polyclinic of RSUP Dr. M. Djamil Padang. The population consisted of 400 people, with 200 participants selected through an accidental sampling technique. The research instruments included the Multidimensional Scale of Perceived Social Support (MSPSS) for social support and the Rosenberg Self-Esteem Scale (RSES) for self-esteem. Ethical approval was obtained from the Health Research Ethics Committee of RSUP Dr. M. Djamil Padang. Data analysis was conducted univariately (frequency distribution tables) and bivariately using the chi-square test. Results: The research found that 49.5% of respondents had high social support, while 87.5% had high self-esteem. A significant relationship was observed between social support and self-esteem (p-value = 0.004). Respondents with higher social support were more likely to report higher self-esteem, indicating the importance of social interactions in shaping psychological well-being. Conclusion: These findings highlight the need for targeted psychosocial interventions to strengthen family and community-based support systems for people with HIV/AIDS. It is recommended that healthcare services actively involve families and close social networks to enhance self-esteem in affected individuals.